EVIDENCE OF COLD SEEPING IN PLIO-PLEISTOCENE SEDIMENTS OF SE PELOPONESE: THE FOSSIL CARBONATE CHIMNEYS OF NEAPOLIS REGION - Sakellariou, D.; Fountoulis, I.; Lykousis, V. (Bulletin of the Geological Society of Greece, 2010)
Unique, upright standing, chimney-like structures outcropping in (Plio-)Pleistocene sediments of Neapolis region, SE Peloponese are studied thoroughly. The up to 5m high and 3m wide structures, previously interpreted either as “rhizoliths” or hypercalcified giant sponges or fossilized palm trees, display a wide range of morphological types and are composed of hard, several cm thick, carbonate tube. Their orifice is filled up with muddy, sandy or fine conglomerate material, which reflects the sedimentary nature of the surrounding formation, and is penetrated by numerous whitish, mm-thin, carbonate veins. Their formation and spatial occurrence is genetically associated with two intersecting systems of diaclases/fractures, also sealed with carbonate material. We interpret these structures as non-volcanic, fossil, gas chimneys, related to cold seeping (biogenic methane? seeping). The intersecting diaclases have been used as conduits for the upward fluid migration, thus, the gas seeping process must have taken place after the diagenesis of the host sedimentary formations. The impressive outcrops of carbonate gas chimneys in the Neapolis region is the first evident of cold seeping, eventually related with mud volcanism, in the Plio-Pleistocene sedimentary basins of the Hellenic Forearc.